Lampung Natural Zeolite Dopped with of ZnO-TiO2 Metal Oxide as Catalyst for Biodiesel Production - Al Muttaqii, Muhammad; Marbun, Maja Pranata; Priyanto, Sugeng; Sibuea, Andreas; Simanjuntak, Wasinton; Syafaat AM, Fuad; Silalahi Raja, Havier Samuel Huttur; Alviany, Riza; Maryani, Tri; Sulistyaningsih, Triastuti; Prasetyo, Erik; Sudibyo, Sudibyo; Yati, Indri (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
Research has been carried out on making biodiesel from palm oil using natural zeolite catalysts impregnated with metal oxides such as zinc oxide and titanium oxide. This research aims to produce biodiesel using natural zeolite and ZnO-TiO2/NZ catalysts. The catalysts were analyzed using X-Ray Diffraction (XRD), X-Ray Fluorescence (XRF), Scanning Electron Microscope (SEM), and Brunauer-Emmet-Teller (BET). The catalyst was tested in the transesterification reaction to produce biodiesel. The mole oil and methanol ratio varied from 1:15, 1:18, and 1:20. In addition, the biodiesel product was analyzed using Gas Chromatography-Mass Spectroscopy (GC-MS). The results showed the optimum condition for converting triglycerides to 1:18 variation of oil:methanol was 60.53%using a ZnO-TiO2/NZ catalyst. The ZnO-TiO2/NZ catalyst is very promising for use as a catalyst for converting palm oils into biodiesel.